(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to create a radio-frequency identification and near-field communication door lock. To be able to provide access to the students, professors, staff, and other individuals. This is convenient right now and in the future. Over traditional lock and key access in schools, keyless access locks have a number of benefits. Electronic door locks with RFID capabilities offer convenience and improved security to clients. RFID key cards offer security against unauthorized users because they are significantly more difficult to replicate than keys. RFID technology not only offers a great level of protection, but it is also incredibly user-friendly. The researchers designed the Radio Frequency Identification and Near Field Communication Door Lock for Bloomridge Integrated School to have a more secure lock. The proponents have found a solution for the client’s problem with the help of radio frequency identification and a near-field communication door lock for their school. They are delighted that the researcher developed a more secure lock for their facility for the safety of the faculty, employees, and students. Radio-frequency Identification Technology communicates between two devices, tags, and readers, using electromagnetic fields. Radio-frequency identification door locks operate by establishing a connection between credentials and the reader via radio waves. Access control providers have discovered the wireless capabilities and flexibility of RFID technology to be valuable, going beyond the standard lock and key.